Brasilien am Main gekreuzte Wege : encrucilhadas : performative Forschungsreisen auf den Spuren der anderen - Barboza, Amalia 1972- (Postcolonial Studies, 2019)
Brazil on the Main is a research trip that explores the country of Brazil based of its migrants to Frankfurt. Amalia Barboza develops an intercultural, performative and relational approach between sociology and artistic research